Joint Human Detection and Head Pose Estimation via Multistream Networks for RGB-D Videos - Guyue Zhang; Jun Liu; Hengduo Li; Yan Qiu Chen; Davis, Larry S. (IEEE signal processing letters, 2017)
We propose a multistream multitask deep network for joint human detection and head pose estimation in RGB-D videos. To achieve high accuracy, we jointly utilize appearance, shape, and motion information as inputs. Based on the depth information, we generate scale invariant proposals, which are then fed into a novel contextual region of interest pooling (CRP) layer in our deep network. This CRP has two branches to deal with contextual information for each subject. The proposed method outperforms state-of-the-art approaches on three public datasets.